Study of Scientific Interpretation in Indonesia: A Study of Scientific Interpretation by the Ministry of Religion - Ilham Fajar; Yayan Mulyana (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the study of scientific interpretation in Indonesia by examining the scientific interpretation of the work of the Ministry of Religion. This research method is a qualitative type through literature study with content analysis. The research discussion includes a general view of scientific interpretation, a study of scientific interpretation in Indonesia, and a study of scientific interpretation by the Ministry of Religion of the Republic of Indonesia. This study concludes that Tafsir 'ilmi is a process of explaining the verses of the Qur'an using a scientific style or approach in an effort to understand the content of the Qur'an based on scientific theories. Many studies of scientific interpretation in Indonesia have been carried out from the 1960s until now, a concrete example is the scientific interpretation by the Ministry of Religion. The Ministry of Religion, which is the government's right-hand man in assisting the government in the field of Religion, from 2010 to 2016 has published 19 themes of various interpretations.